Uji Efektivitas Antibakteri Ekstrak Daun Kamboja (Plumiera rubra) pada Konsentrasi yang Berbeda Terhadap Pertumbuhan Aeromonas hydrophila secara In Vitro - Wan Nita Ulfani Barus; Hasan Sitorus; Indra Lesmana (AQUACOASTMARINE, 2013)
Indonesia the outbreaks of disease in red spotted fish is caused byA.hydrophila bacteria. Many efforts have been made by the experts to address thisoutbreak by both giving vitamins and giving probiotics and antibiotics. However aprolonged uncontrolled usage and improper dosage may lead to negative impactsto the species. Thus, the use of medicinal plants or fitofarmaka is a solution toovercome these problems. This research aims to know the effectiveness ofFrangipani leaf extract (Plumeira rubra) on the growth of bacteria A. hydrophilaand to determine the minimum dose of Frangipani leaf extract necessary to inhibitthe growth of bacteria. The research was conducted at Laboratory of FishQuarantine, Quality Control and Fisheries Product Safety Level I, Medan I. Theresearch used a completely randomized experiment method with 6 treatmentlevels and 3 replications. The research shows that, the Frangipani leaf extractdoses has highly significant effect on the growth of bacteria A .hydrophila, andthe minimum dose to inhibit the bacteria is 2 % with a clear zone diameter of 6.4mm.Key words : Effectiveness , Frangipani leaf extract, A. hydrophila